Morphology-dependent entry kinetics and spread of influenza A virus - Peterl, Sarah; Lahr, Carmen M.; Schneider, Carl N.; Meyer, Janis; Podlipensky, Xenia; Lechner, Vera; Villiou, Maria; Eis, Larissa; Klein, Steffen; Funaya, Charlotta; Cavalcanti-Adam, Elisabetta A.; Graw, Frederik; et al. (The EMBO journal, 2025)
Influenza A viruses (IAV) display a broad variety of morphologies ranging from spherical to long filamentous virus particles. These diverse phenotypes are believed to allow the virus to overcome various immunological and pulmonary barriers during entry into the airway epithelium, and to influence the viral entry pathway. Notably, laboratory-adapted IAV strains predominantly adopt a spherical form, yet the factors driving this preference as well as the factors favoring filamentous morphology in physiological settings remain unclear. To address this, we generated fluorescent reporter viruses with identical surface glycoproteins but distinct morphologies and developed a correlative light and scanning electron microscopy workflow. This enabled us to investigate the impact of viral morphology on spread, and to identify conditions favoring either form. Our findings demonstrate that filamentous IAV spread significantly slower in various cell lines, consistent with delayed entry kinetics and in-cell cryo-electron tomography, explaining the predominance of spherical forms in laboratory-adapted strains. Cellular junction integrity, neuraminidase activity, and mucin do not inhibit IAV spread in a morphology-dependent manner. However, filamentous virions confer a selective advantage under neutralizing-antibody pressure against hemagglutinin.
Online veröffentlicht: 9 June 2025
Gesehen am 27.10.2025